Genetic Diversity Using Random Amplified Polymorphic DNA (RAPD)Analysis for Aspergillus niger isolates - Hashoosh, Qadisiyah; Al-Araji, Alaa; Al-Assie, Akeel (Iraqi Journal of Science, 2025)
This study includes isolation, purification, and identification of Aspergillus nigerfrom different sources (soil, Seeds, powdered milk and factory waste water) bytraditional methods (macroscopic and microscopically). and study the relationshipsof genetic among the A. niger isolates based PCR (RAPD) technique (find the DNAfingerprint). The results of this study revealed that genetic diversity andrelationships among twenty four isolates were determined by using the randomamplified polymorphic DNA (RAPD) technique. Genomic DNA of each isolateswas extract at final concentration of (115-959) μg /l per (2-3) gm of wet mycelium,and at a purity (1.7-1.9). Each DNA of isolates were amplified with each 24 primersand the products were resolved electrophoretically on 1.2% agarose gel, stained withethidium bromide and photographed under UV light. Ten primers failed to amplifyDNA of A. niger isolates but the rest 14 primers produced 367 bands, of these bands99.4% (365) bands were polymorphic. The size of the amplified bands rangedbetween 130-2840 bp. The genetic polymorphism value of each primer wasdetermined and ranged between 86-100%. All primer have given unique bands. Theprimers were fingerprinted 21 of the 24 isolates. Genetic distances ranged from0.11496 to 0.68088 between A. niger isolates. Also, cluster analysis of geneticdistances between these isolates have divided into groups according to the source,which isolated them and this indicates the presence of a high level of genetic kinshipsamples isolated from the same source at the same time which indicates thepresence of a high level of genetic distance between samples isolated from differentsources.